Nation‐building policies in Timor‐Leste: disaster risk reduction, including climate change adaptation. Issue 4 (October 2014) - Mercer, Jessica; Kelman, Ilan; do Rosario, Francisco; de Deus de Jesus Lima, Abilio; da Silva, Augusto; Beloff, Anna‐Maija; McClean, Alex
<x xml:space="preserve">Abstract</x> Few studies have explored the relationships between nation‐building, disaster risk reduction and climate change adaptation. Focusing on small island developing states, this paper examines nation‐building in Timor‐Leste, a small island developing state that recently achieved independence. Nation‐building in Timor‐Leste is explored in the context of disaster risk reduction, which necessarily includes climate change adaptation. The study presents a synopsis of Timor‐Leste's history and its nation‐building efforts as well as an overview of the state of knowledge of disaster risk reduction including climate change adaptation. It also offers an analysis of significant gaps and challenges in terms of vertical and horizontal governance, large donor presence, data availability and the integration of disaster risk reduction and climate change adaptation for nation‐building in Timor‐Leste. Relevant and applicable lessons are provided from other small island developing states to assist Timor‐Leste in identifying its own trajectory out of underdevelopment while it builds on existing strengths.